The Importance of Remittances as a Foreign Source of Financing in Kosovo: Array - Merovci, Safet; Sekiraqa, Albina (Acta Universitatis Danubius. Œconomica, 2021)
This paper aims to present the importance and effect of remittance flows in the context of receiving foreign funds. Remittances from Kosovar migrants constitute one of the most important source of the foreign flows and in microeconomic terms represent one of the most important sources of households income because of the great dependence of households on them. This paper will also present data and analysis regasrding to the trend of migration and remittances, influenced factors on variable phenomena, the importance of remittance flows in macro and micro economic terms. The paper finds that remittances are not only related to remittances flows to Kosovo, but also with other contribution forms such as expenses, money, purchases and other expenses they execute during their stay in Kosovo; remittance flows are significant as a share of GDP. This share is the highest in the region. The paper also shows how remittances have a very important role in mitigating the balance of payments deficit.